Induced polarization effects in airborne transient electromagnetic data collected in the McMurdo Dry Valleys, Antarctica. Issue 3 (5th May 2021) - Grombacher, Denys; Auken, Esben; Foged, Nikolaj; Bording, Thue; Foley, Neil; Doran, Peter T; Mikucki, Jill; Dugan, Hilary A; Garza-Giron, Ricardo; Myers, Krista; Virginia, Ross A; Tulaczyk, Slawek
SUMMARY: Airborne electromagnetics (EM) is a geophysical tool well suited to mapping glacial and hydrogeological structures in polar environments. This non-invasive method offers significant spatial coverage without requiring access to the ground surface, enabling the mapping of geological units to hundreds of metres depth over highly varied terrain. This method shows great potential for large-scale surveys in polar environments, as common targets such as permafrost, ice and brine-rich groundwater systems in these settings can be easily differentiated because of their significant contrasts in electrical properties. This potential was highlighted in a 2011 airborne EM survey in the McMurdo Dry Valleys that mapped the existence of a large-scale regional groundwater system in Taylor Valley. A more comprehensive airborne EM survey was flown in November 2018 to broadly map potential groundwater systems throughout the region. Data collected in this survey displayed significant perturbations from a process called induced polarization (IP), an effect that can greatly limit or prevent traditional EM workflows from producing reliable geological interpretations. Here, we present several examples of observed IP signatures over a range of conditions and detail how workflows explicitly designed to handle IP effects can produce reliable geological interpretations and data fits in these situations. Future polar EM surveys can be expected to encounter strong IP effects given the likely presence of geological materials (e.g. ice and permafrost) that can accentuate the influence of IP.